Preparation of Porous Silicon by Electrochemical Etching in the Fabrication of a Solar Cell - Magentharau, Adin Naraina (2003)
Porous silicon samples have been prepared using electrochemical etching technique. In this project, a 3 cm x 5cm single crystal p-type silicon wafer <422>, resistivity 19.64 Ωcm with thickness of 200µm was used to prepare porous silicon. The silicon was etched in an aqueous solution at the current density of 5 mA/cm² for 30 minutes under illumination of a 1OOW halogen lamp at room temperature. The SEM, EDAX and XRD analysis were carried out to exhibit the physical properties of porous silicon. Then the porous silicon was doped with n-type material (Sb) and diffused at temperature of 600°C for 15 minutes to form p-n junction. The prepared sample was deposited with Aluminium at back and front of the sample to form electrical contact. The porous silicon solar cells were measured for efficiency using a sun simulator. From the SEM analysis, the morphology exhibit the island type surface and EDAX analysis which shows oxide layers are mainly incorporated near the surface of porous silicon. The XRD results revealed that the peak had widened and x-ray counts increased. Finally, an efficiency measurement was conducted to determine the efficiency of the designed porous silicon cell. The highest efficiency percentage achieved for prepared porous silicon cell is 10.5% only compared to current solar cells GaAs which can achieve up to 31.0% percent.